Pengaruh terapi komplementer dengan mendengarkan murotal Al-Qur’an terhadap tingkat kecemasan pada mahasiswa tingkat akhir yang menyusun skripsi dimasa pandemi Covid-19 - Karimah, Nurlita; Maulana, Nova (Health Sciences and Pharmacy Journal, 2022)
Covid-19 is a new type of virus discovered in 2019. The Covid-19 pandemic raises anxiety and concern about the situation happening in the Covid-19 pandemic, which could decrease a person's health level, including among students at the final level. Murotal Al-Qur’an can also reduce fear, anxiety, and tension. This study aims to determine the effect of complementary therapy by listening to the Murotal Al-Quran on the level of anxiety in final-year students who are writing a thesis in a Covid-19 pandemic situation. This study used an experimental research design with a quasi-experimental design using a non-randomized pretest-Post-test with a control group design. The population in this study were seventh-semester nursing students at STIKes Surya Global Yogyakarta who were working on a thesis. A total of 30 people used a simple random sampling technique. Univariate and bivariate analysis with Wilcoxon test and Mann Whitney statistical test. After the Wilcoxon non-parametric test was carried out on the anxiety level of students in the intervention group, the results were a p-value of 0.001 (p <0.05), while in the control group with a p-value of 1.157 (p>0.05). In Mann-Whitney testing, the writer obtained results in the intervention group, namely the p-value of 0.006 <0.05, while in the control group, the p-value of 0.668> 0.05. There is an effect of Al-Qur’an Murotal therapy on the anxiety level of final-year students who are working on their thesis during the Covid-19 Pandemic at STIKes Surya Global Yogyakarta